Dual Role of Bacteria in Carcinoma: Stimulation and Inhibition - Suad A Al-Hilu; Wisam H Al-Shujairi (International Journal of Microbiology)
Although what unifies the carcinogenic microorganisms has not been determined by multiple studies, the role of bacteria in the development of neoplasms has not been properly elucidated. In this review, we discuss links between the bacterial species and cancer, with focus on immune responses for the stimulation of tumor cells such as induction of inflammation. Finally, we will describe the potential therapeutic strategies of bacteria on target tumors to improve treatment while mitigating adverse reactions. Cancer is a series of genetic changes that transform normal cells into tumor cells. These changes come from several reasons, including smoking, drinking alcohol, sunlight, exposure to chemical or physical factors, and finally chronic infection with microorganisms, including bacteria. In fact, bacterial infections are not carcinogenic, but recently it was discovered that the association between bacteria and cancer is through two mechanisms, the first stimulating chronic inflammation and the second producing carcinogenic metabolites. While bacteria are carcinogenic agents also, they have a dual role eliminating and removing tumor cells. However, the traditional cancer treatments that include chemotherapy, radiotherapy, surgery, and immunotherapy increase the chances of survival, and there are many side effects of these therapies, including the high toxicity of tissues and normal cells, could not penetrate the tumor cells, and resistance of these therapies by tumor cells. Therefore, the world has turned to an alternative solution, which is the use of genetically engineered microorganisms; thus, the use of living bacteria targeting cancerous cells is the unique option to overcome these challenges. Bacterial therapies, whether used alone or combination with chemotherapy, give a positive effect to treat multiple conditions of cancer. Also, bacteria can be used as vectors for drug, gene, or therapy, and this is a great step to treat cancer. Thus, we review the mechanisms underlying the interaction of the microbiota residents with cancer. Cancer-associated bacteria differ from those in healthy human and are linked with gene-expression profile. We also discuss how live bacteria interact with tumor microenvironments to induce tumor regression through colonization and spread. Finally, we provide past and ongoing clinical trials that include bacteria targeting tumors.